Le CIEPAC* à la croisée des réseaux militants globalisés : la réticule comme forme organisationnelle de la globalisation - Jean Foyer (Cahiers des Amériques Latines)
From the case of a local organisation, CIEPAC, we try to show the main transformations of the militant organisations, in particular of those who pronounce themselves against economical liberalism. Mutations are observed both in the nature of militants who now tend to act as experts and in their formerly territorial and sector-based logic of mobilisation. Militancy seems to globalise in two ways: first, its activities tend to take place between the local and the global levels, over the frameworks of Nation-States ; second, the matters of mobilisation are intertwining more and more. In this context of globalisation, understood as a meta-process of integration, it may be that the network, precisely because of its integrative virtues (connectivity, flexibility, informality…), becomes the main and favourite form of organisation, contrary to bureaucratic and institutional structures.